Pemberdayaan UMKM dalam Legalitas Usaha melalui Pembuatan NIB di Kecamatan Rungkut - Muhammad Ilham Nadzir; Nurkholish Majid (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in promoting economic growth and employment absorption. However, many MSME actors in Rungkut District, Surabaya City, still do not have business legality, particularly the Business Identification Number (Nomor Induk Berusaha/NIB). This condition is caused by a low level of understanding regarding the importance of business legality and limited ability to use the online business licensing system through the Online Single Submission Risk-Based Approach (OSS-RBA). Therefore, this community service activity aims to enhance the knowledge and capacity of MSME actors in managing business legality through the issuance of NIB. The implementation methods include delivering materials on the importance of business legality, training on the use of the OSS-RBA platform, direct assistance in the NIB registration process, and activity evaluation. The results indicate an increase in MSMEs' understanding of the importance of business legality as well as an improvement in participants' ability to obtain NIB, with most participants successfully acquiring NIB after the mentoring activities. This activity is expected to encourage greater business formalization and strengthen the competitiveness of MSMEs in Rungkut District.